Phosphor plate and light emitting device using the same

By optimizing the absorption parameters and structural indicators of the phosphor plate, reducing the self-absorption phenomenon in the luminescent area, the problem of reducing the fluorescence intensity of the existing phosphor plates is solved, and higher fluorescence intensity and brightness are achieved.

CN113993974BActive Publication Date: 2025-02-11DENKA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080045123.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-06-22
Publication Date
2025-02-11
Estimated Expiration
2040-06-22

AI Technical Summary

Technical Problem

The self-absorption phenomenon of existing fluorescent plates during luminescence leads to a decrease in fluorescence intensity, and the influence of its complex structure on fluorescence intensity has not been fully studied.

Method used

By optimizing the structural parameters of the phosphor plate, including setting the absorption rate of 455 nm to A455 (%) and the absorption rate of 700 nm to A700 (%), and using the (A700/A455)/T indicator to stably evaluate the degree of non-luminescent absorption , thereby reducing self-absorbing and improving fluorescence intensity.

Benefits of technology

It is possible to increase the fluorescence intensity of the phosphor plate within an appropriate range, suppress non-luminescence absorption of the luminescent region, and enhance the brightness of the luminescent device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113993974B_ABST
    Figure CN113993974B_ABST
Patent Text Reader

Abstract

The phosphor plate of the present invention comprises a plate-shaped composite body including a base material and phosphors dispersed in the base material, and the absorbance at 455 nm when measuring the absorption spectrum of light with a wavelength of 300 nm to 700 nm is defined as A. 455 (%), the absorbance at 700 nm is set as A 700 (%), when the thickness of the phosphor plate is T (mm), (A 700 / A 455 ) / T satisfies 0.01~1.00.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a phosphor plate and a light emitting device using the phosphor plate. Background Art

[0002] Various phosphor plates have been developed so far. As such a technology, for example, the technology described in Patent Document 1 is known. Patent Document 1 describes a phosphor plate in which YAG:Ce crystal grains and alumina crystal grains are mixed as an example (paragraph 0055 of Patent Document 1, etc.).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2012-9470 Summary of the invention

[0006] However, the present inventors have conducted studies and have found that the phosphor plate described in Patent Document 1 has room for improvement in terms of fluorescence intensity.

[0007] The phosphor plate composed of a composite body including a base material and a phosphor has not been fully studied in the above-mentioned Patent Document 1. In a phosphor plate, when light is emitted, if the self-absorption of light emitted increases, the fluorescence intensity may decrease.

[0008] The inventors conducted further research and found that the reduction in fluorescence intensity can be suppressed by reducing the self-absorption of luminescence in the luminescent area caused by the phosphor plate, so-called non-luminescent absorption, and the absorbance at 700nm can be used as an indicator of the degree of non-luminescent absorption.

[0009] Based on this insight, we conducted further research and found that by setting the absorbance at 455 nm to A 455 (%), the absorbance at 700 nm is set to A 700 (%), when the thickness of the phosphor plate is T (mm), (A 700 / A 455 ) / T as an indicator, the degree of non-luminescent absorption can be stably evaluated. By keeping this indicator within an appropriate range, the fluorescence intensity of the phosphor plate can be improved, thereby completing the present invention.

[0010] According to the present invention, there is provided a phosphor plate,

[0011] A plate-shaped composite body including a base material and a phosphor dispersed in the base material,

[0012] When the absorption spectrum of light with a wavelength of 300 nm to 700 nm is measured for this phosphor plate, the absorbance at 455 nm is defined as A.455 (%), the absorbance at 700 nm is set as A 700 (%), when the thickness of the phosphor plate is T (mm),

[0013] (A 700 / A 455 ) / T satisfies 0.01~1.00.

[0014] In addition, according to the present invention, there can be provided a light emitting device comprising:

[0015] A Group III nitride semiconductor light emitting device, and

[0016] The above-mentioned phosphor plate is provided on one surface of the above-mentioned Group III nitride semiconductor light-emitting element.

[0017] According to the present invention, a phosphor plate having excellent fluorescence intensity and a light-emitting device using the phosphor plate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram showing an example of the structure of the phosphor plate of this embodiment.

[0019] Figure 2 (a) is a cross-sectional view schematically showing the structure of a flip-chip type light-emitting device, and (b) is a cross-sectional view schematically showing the structure of a wire bonding type light-emitting element.

[0020] Figure 3 This is a schematic diagram of an apparatus for measuring the emission spectrum of a complex. DETAILED DESCRIPTION

[0021] Hereinafter, the embodiments of the present invention will be described using the accompanying drawings. It should be noted that in all the accompanying drawings, the same components are marked with the same symbols, and the description is appropriately omitted. In addition, the drawings are schematic diagrams and do not correspond to the actual size ratios.

[0022] The outline of the phosphor plate of this embodiment will be described.

[0023] The phosphor plate of the present embodiment is composed of a plate-like member including a plate-like composite body including a base material and phosphors dispersed in the base material.

[0024] In the phosphor plate, the main component of the base material is alumina, and the phosphor may include an α-sialon phosphor.

[0025] Such a phosphor plate can function as a wavelength converter that converts irradiated blue light into orange light to emit light.

[0026] In the phosphor plate of this embodiment, (A 700 / A455 ) / T satisfies 0.01~1.00.

[0027] Here, when measuring the absorption spectrum of light with a wavelength of 300 nm to 700 nm for the phosphor plate, the absorbance at 455 nm is defined as A. 455 (%), the absorbance at 700 nm is set as A 700 (%), and the thickness of the phosphor plate is denoted as T (mm).

[0028] A 455 This represents a representative value of light absorption of the excitation light (blue light) irradiated to the phosphor plate.

[0029] A 700 This value represents the representative value of the non-luminescent absorption that does not contribute to the luminescence of the phosphor plate, among the light absorption of the phosphor plate.

[0030] According to the present inventors' knowledge, it was found that by adopting (A 700 / A 455 ) / T as an index, the degree of non-luminescent absorption of the phosphor plate containing the α-sialon phosphor can be stably evaluated, and by using (A 700 / A 455 ) / T is within the above range, the fluorescence intensity of the phosphor plate can be improved.

[0031] (A 700 / A 455 ) / T is less than 1.00, preferably less than 0.95, and more preferably less than 0.90. This can improve the fluorescence intensity of the phosphor plate. The light emission from the phosphor plate in the light-emitting region near 600nm to 700nm can be suppressed from being absorbed by itself, so-called self-absorption of light emission, thereby suppressing the reduction of its fluorescence intensity.

[0032] On the other hand, (A 700 / A 455 The lower limit of ) / T is not particularly limited and may be 0.01 or more.

[0033] In this embodiment, for example, by appropriately selecting the type and amount of each component contained in the phosphor plate, the method for manufacturing the phosphor plate, etc., the above (A) can be controlled. 700 / A 455 ) / T. Among these, as a method for making the above (A 700 / A 455 ) / T is a factor in the desired numerical range, and examples thereof include the ability to appropriately adjust the specific surface area of ​​the alumina powder used as the raw material, the heating temperature of the calcination step, the content ratio of the phosphor in the composite, and the like.

[0034] The detailed mechanism is not clear yet, but it is considered that non-luminescent absorption can be reduced by suppressing the blackening of the phosphor plate or the like.

[0035] In addition, according to the present embodiment, the phosphor plate including the α-sialon phosphor and alumina is preferably configured such that when irradiated with blue light having a wavelength of 455 nm, the peak wavelength of wavelength-converted light emitted from the phosphor plate is 585 nm to 605 nm. By combining such a phosphor plate with a light-emitting element that emits blue light, a light-emitting device that emits orange light with high brightness can be obtained.

[0036] Hereinafter, the phosphor plate of this embodiment will be described in detail.

[0037] In the composite constituting the above-mentioned phosphor plate, a phosphor (α-type Sialon phosphor) and a base material (alumina) are mixed. Mixed existence refers to a state in which the phosphor (α-type Sialon phosphor) is dispersed in the alumina that becomes the base material (matrix phase). That is, the composite can have a structure in which α-type Sialon phosphor particles are dispersed between the grains and / or within the grains of the (poly) crystalline body constituted by the base material. The α-type Sialon phosphor particles can be uniformly dispersed in the base material (alumina sintered body).

[0038] The phosphor may include an α-sialon phosphor represented by the following general formula (1).

[0039] (M) m(1-x) / p (Eu) mx / 2 (Si) 12-(m+n) (Al) m+n (O) n (N) 16-n ··General formula (1)

[0040] In the above general formula (1), M represents one or more elements selected from Li, Mg, Ca, Y and lanthanide elements (excluding La and Ce), p represents the valence of the M element, 0<x<0.5, 1.5≤m≤4.0, 0≤n≤2.0. For example, n can be 2.0 or less, 1.0 or less, or 0.8 or less.

[0041] The solid solution composition of α-sialon is the unit cell (Si 12 N 16 ) is replaced by Al-N bonds, and n Si-N bonds are replaced by Al-O bonds. In order to maintain electrical neutrality, m / p cations (M, Eu) penetrate and dissolve in the lattice, as shown in the above general formula. In particular, if Ca is used as M, α-sialon is stabilized in a wide composition range, and by replacing a part of it with Eu that becomes the luminescence center, a phosphor that is excited by light in a wide wavelength range from ultraviolet to blue and shows visible light from yellow to orange can be obtained.

[0042] Generally speaking, for α-Sialon, due to the second crystalline phase different from the α-Sialon and the inevitable presence of an amorphous phase, the solid solution composition cannot be strictly defined by composition analysis, etc. As the crystalline phase of α-Sialon, the α-Sialon single phase is preferred, and as other crystalline phases, β-Sialon, aluminum nitride or its polytype (polytypoid), Ca2Si5N8, CaAlSiN3, etc. may be included.

[0043] Here, if the refractive index difference is too small as in the combination of YAG phosphor and alumina, light scattering becomes difficult, and the phosphor content needs to be increased in order to prevent the transmission of blue light.

[0044] In contrast, it is considered that the refractive index difference between the α-sialon phosphor and alumina is moderately large, and the scattering of blue light is promoted, and the transmission of blue light can be efficiently suppressed at a low phosphor content, thereby emitting orange light with high brightness.

[0045] As representative values ​​of the refractive index of each component, it is known that α-sialon phosphor: about 2.0, YAG phosphor: about 1.8, Al2O3: about 1.7, and SiO2: about 1.4.

[0046] As a method for producing an α-sialon phosphor, there is a method of heating a mixed powder composed of silicon nitride, aluminum nitride, and a compound infiltrated with a solid solution element in a high-temperature nitrogen atmosphere to cause the mixture to react.

[0047] In the heating step, a part of the components forms a liquid phase, and the substances migrate in the liquid phase, thereby generating an α-sialon solid solution. A plurality of equiaxed primary particles of the synthesized α-sialon phosphor are sintered to form bulk secondary particles.

[0048] The primary particle in this embodiment refers to the smallest particle that has the same crystal orientation within the particle and can exist independently.

[0049] The lower limit of the average particle size of the α-sialon phosphor is preferably 5 μm or more, more preferably 10 μm or more. On the other hand, the upper limit of the average particle size of the α-sialon phosphor is preferably 40 μm or less, more preferably 30 μm or less. The average particle size of the α-sialon phosphor is the size of the secondary particles.

[0050] When the average particle size of the α-sialon phosphor is 5 μm or more, the transparency of the composite can be further improved. On the other hand, when the average particle size of the α-sialon phosphor is 40 μm or less, the generation of chips can be suppressed when the phosphor plate is cut by a dicer or the like.

[0051] Here, the average particle size of the α-sialon phosphor refers to the particle size D at which the cumulative amount of passing through from the small particle size side (cumulative passing fraction) is 50% in the volume-based particle size distribution measured by laser diffraction scattering particle size distribution measurement method (manufactured by Beckman Coulter, LS13-320). 50 .

[0052] The lower limit of the content of the α-type Sialon phosphor is, for example, 5 Vol% or more, preferably 10 Vol% or more, and more preferably 20 Vol% or more, calculated by volume in the entire composite. Thus, the fluorescence intensity of the thin layer of the phosphor plate can be increased. In addition, the light conversion efficiency of the phosphor plate can be improved. On the other hand, the upper limit of the content of the α-type Sialon phosphor is, for example, 60 Vol% or less, preferably 55 Vol% or less, and more preferably 50 Vol% or less, calculated by volume in the entire composite. Thus, the reduction in thermal conductivity of the phosphor plate can be suppressed. The content of the phosphor can also be within the same range as the above-mentioned upper limit and the above-mentioned lower limit of the content of the α-type Sialon phosphor.

[0053] The base material contained in the composite can be composed of a sintered body of aluminum oxide. Aluminum oxide in the sintered body absorbs less visible light, so it can improve the fluorescence intensity of the phosphor plate. In addition, aluminum oxide has high thermal conductivity, so it can improve the heat resistance of the phosphor plate containing aluminum oxide. Furthermore, aluminum oxide also has excellent mechanical strength, so it can improve the durability of the phosphor plate.

[0054] From the viewpoint of light extraction efficiency, the aluminum oxide in the sintered body preferably has fewer impurities. For example, in the aluminum oxide in the sintered body, the purity of the Al2O3 compound can be, for example, 98 wt% or more, preferably 99 wt% or more.

[0055] The aluminum oxide in the sintered body may include one or more selected from α-alumina and γ-alumina. This can improve the light conversion efficiency of the phosphor plate.

[0056] The lower limit of the content of the α-sialon phosphor and aluminum oxide is, for example, 95 Vol% or more, preferably 98 Vol% or more, and more preferably 99 Vol% or more in terms of volume conversion in the entire composite. That is, heat resistance and durability can be improved, and stable luminous efficiency can be achieved. On the other hand, the upper limit of the content of the α-sialon phosphor and aluminum oxide is not particularly limited, and for example, it can be 100 Vol% or less in terms of volume conversion in the entire composite.

[0057] The contents of the phosphor and aluminum oxide may be within the same ranges as the above upper limits and the above lower limits of the contents of the α-sialon phosphor and aluminum oxide.

[0058] The lower limit of the thermal conductivity of the phosphor plate is, for example, 10 W / m·K or more, preferably 15 W / m·K or more, and more preferably 20 W / m·K or more. This allows high thermal conductivity to be achieved, and thus allows a phosphor plate with excellent heat resistance to be achieved. On the other hand, the upper limit of the thermal conductivity of the phosphor plate is not particularly limited, and may be, for example, 40 W / m·K or less.

[0059] In recent years, it is known that the temperature of phosphors tends to increase due to the increase in the brightness of light sources. In such a case, it is possible to stably emit high-brightness orange light by using a phosphor plate having excellent thermal conductivity.

[0060] At least the main surface or both the main surface and the back surface of the phosphor plate may be subjected to surface treatment. Examples of the surface treatment include grinding using a diamond wheel, polishing, buffing, and the like.

[0061] An example of a process for producing the phosphor plate of the present embodiment will be described.

[0062] The manufacturing method of the phosphor plate of this embodiment may have the following steps: step (1), mixing aluminum oxide powder and α-type Sialon phosphor powder containing at least Eu element as the luminescence center; step (2), heating the mixture of aluminum oxide powder and α-type Sialon phosphor powder to calcine a dense composite.

[0063] In step (1), the alumina powder and α-sialon phosphor powder used as raw materials are preferably as pure as possible, and the impurities of elements other than the constituent elements are preferably 0.1% or less. The raw material powders can be mixed by various methods such as dry and wet methods, but it is preferred to use a method that minimizes the crushing of the α-sialon phosphor particles used as raw materials and minimizes the mixing of impurities from the device during mixing.

[0064] The upper limit of the BET specific surface area of ​​the alumina powder used as a raw material is, for example, 10.0 m 2 / g or less, preferably 9.0m 2 / g or less, more preferably 8.0m 2 / g or less, more preferably 6.0m 2 / g. This can suppress the blackening of the phosphor plate. On the other hand, the lower limit of the BET specific surface area of ​​the alumina powder is, for example, 0.1 m 2 / g or more, preferably 0.5m 2 / g or more, more preferably 1.0 m 2 / g or more, more preferably 2.0m 2 This can improve the sinterability of the alumina powder and form a dense composite.

[0065] In step (2), the mixture of alumina powder and α-sialon phosphor powder is calcined at 1300° C. to 1700° C. The heating temperature of the sintering step is more preferably 1500° C. or higher. In order to densify the composite, the calcination temperature is preferably high, but if the calcination temperature is too high, the phosphor reacts with alumina and the fluorescence intensity of the phosphor plate decreases, so the above range is preferred.

[0066] The calcination method may be pressureless sintering or pressured sintering. However, in order to suppress the degradation of the characteristics of the α-sialon phosphor and obtain a dense composite, pressured sintering is preferred because it is easier to densify than pressureless sintering.

[0067] Examples of the pressure sintering method include hot pressing, spark plasma sintering (SPS), hot isostatic pressing (HIP), etc. In the case of hot pressing and SPS, the pressure is 10 MPa or more, preferably 30 MPa or more, and preferably 100 MPa or less.

[0068] In order to prevent oxidation of α-sialon, the calcination atmosphere is preferably a non-oxidizing inert gas such as nitrogen or argon or a vacuum atmosphere.

[0069] Through the above operations, the phosphor plate of this embodiment is obtained.

[0070] The surface of the plate-like composite in the obtained phosphor plate may be subjected to a known surface treatment such as polishing treatment, plasma treatment, surface coating treatment, etc. within a range that does not impair the effects of the present invention.

[0071] The light emitting device of this embodiment will be described.

[0072] The light emitting device of this embodiment includes a group III nitride semiconductor light emitting element (light emitting element 20) and the above-mentioned phosphor plate 10 provided on one side of the group III nitride semiconductor light emitting element. The group III nitride semiconductor light emitting element is an element composed of a group III nitride semiconductor such as AlGaN, GaN, InAlGaN-based materials, and includes an n-layer, a light emitting layer, and a p-layer. As the group III nitride semiconductor light emitting element, a blue LED that emits blue light can be used.

[0073] The phosphor plate 10 may be directly disposed on one surface of the light emitting element 20 or may be disposed via a light-transmitting member or a spacer.

[0074] The phosphor plate 10 disposed on the light emitting element 20 can be used Figure 1 As the disk-shaped phosphor plate 100 (phosphor wafer) shown, a phosphor plate obtained by dividing the phosphor plate 100 into pieces can be used.

[0075] Figure 1Schematic diagram showing an example of the structure of a phosphor plate. Figure 1 The thickness of the phosphor plate 100 shown may be, for example, 100 μm to 1 mm. The thickness of the phosphor plate 100 may be appropriately adjusted by grinding or the like after being obtained in the above-mentioned manufacturing process.

[0076] Note that the disc-shaped phosphor plate 100 can suppress the occurrence of chips and cracks at the corners compared to the case of a quadrilateral shape, and thus is excellent in durability and transportability.

[0077] An example of the above-mentioned semiconductor device is shown in Figure 2 (a), (b). Figure 2 (a) is a cross-sectional view schematically showing the structure of a flip-chip type light emitting device 110. Figure 2 (b) is a cross-sectional view schematically showing the structure of the wire bonding type light emitting device 120 .

[0078] Figure 2 The light emitting device 110 of (a) comprises a substrate 30, a light emitting element 20 electrically connected to the substrate 30 via a solder 40 (die bond material), and a phosphor plate 10 provided on the light emitting surface of the light emitting element 20. The flip chip type light emitting device 110 may be a face-up type or a face-down type.

[0079] in addition, Figure 2 The light emitting device 120 of (b) includes a substrate 30 , a light emitting element 20 electrically connected to the substrate 30 via a bonding wire 60 and an electrode 50 , and a phosphor plate 10 provided on a light emitting surface of the light emitting element 20 .

[0080] Figure 2 In the embodiment, the light emitting element 20 and the phosphor plate 10 are attached to each other by a known method, for example, by a silicone adhesive, thermal welding or the like.

[0081] In addition, the light emitting devices 110 and 120 may be entirely sealed with a transparent sealing material.

[0082] It should be noted that the phosphor plate 10 may be attached to the light emitting element 20 mounted on the substrate 30. After attaching a plurality of light emitting elements 20 to a large-area phosphor plate 100, each light emitting element 20 with the phosphor plate 10 may be diced. Alternatively, the large-area phosphor plate 100 may be attached to a semiconductor wafer having a plurality of light emitting elements 20 formed on the surface, and then the semiconductor wafer and the phosphor plate 100 may be diced together.

[0083] The embodiments of the present invention are described above, but they are illustrative of the present invention, and various configurations other than the above may be adopted. In addition, the present invention is not limited to the above-mentioned embodiments, and modifications and improvements within the scope of achieving the purpose of the present invention are included in the present invention.

[0084] Example

[0085] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited at all to the description of these Examples.

[0086] <Production of phosphor plates>

[0087] (Test Example 1)

[0088] As a raw material of the phosphor plate of Test Example 1, alumina powder (AHP200, manufactured by Nippon Light Metal Co., Ltd., BET specific surface area: 6.0 m 2 / g), Ca-α sialon phosphor (ALONBRIGHT YL-600B, manufactured by Denka Co., Ltd., average particle size D 50 :15μm).

[0089] 7.857 g of alumina powder and 2.833 g of Ca-αsialon phosphor powder were weighed and dry mixed using an agate mortar. The mixed raw materials were passed through a nylon mesh sieve with a mesh size of 75 μm to dissolve the agglomerates and obtain a raw material mixed powder. It should be noted that the true density of the raw materials (alumina: 3.97 g / cm 3 , Ca-αsialon phosphor: 3.34 g / cm 3 ) The calculated mixing ratio is alumina: Ca-α sialon phosphor = 70:30 volume %.

[0090] About 11 g of the raw material mixed powder was filled into a carbon die with an inner diameter of 30 mm and a carbon lower punch, and a carbon upper punch was set to clamp the raw material powder. It should be noted that a carbon sheet (GRAFOIL, manufactured by GraTech) with a thickness of 0.127 mm was set between the raw material mixed powder and the carbon fixture to prevent sticking.

[0091] The hot pressing fixture filled with the raw material mixed powder is set in a multi-purpose high-temperature furnace (manufactured by Fuji Electric Industry Co., Ltd., HIMULTI 5000) with a carbon heater. The furnace is evacuated to less than 0.1Pa, and the reduced pressure state is maintained to pressurize the upper and lower punches with a pressurization pressure of 55MPa. The pressurized state is maintained and the temperature is raised to 1600°C at a rate of 5°C per minute. After reaching 1600°C, the heating is stopped, and the mixture is slowly cooled to room temperature and depressurized. Thereafter, the calcined product with an outer diameter of 30mm is recovered, and the outer periphery is ground using a surface grinder and a cylindrical grinder to obtain a disk-shaped phosphor plate with a diameter of 25mm and a plate thickness described in Table 1.

[0092] In addition, the BET specific surface area of ​​the alumina powder is measured based on JIS Z 8830:2013.

[0093] The bulk density of the phosphor plate of Test Example 1 was measured by a method in accordance with JIS-R1634:1998 and the result was 3.729 g / cm 3 The theoretical density of the mixture calculated from the true density of the raw materials and the mix ratio is 3.781 g / cm 3 , therefore, the relative density of the phosphor plate of Test Example 1 is 99.9%.

[0094] The phosphor plate of Test Example 1 was polished and observed under a SEM. As a result, it was observed that Ca-α-sialon phosphor particles were dispersed between the alumina matrix phases.

[0095] (Test Example 2)

[0096] The alumina powder was changed to AKP-3000 (manufactured by Sumitomo Chemical Co., Ltd., BET specific surface area: 4.5 m 2 / g), a disk-shaped phosphor plate having a plate thickness described in Table 1 was obtained in the same manner as in Test Example 1 except for the above.

[0097] (Test Example 3)

[0098] The alumina powder was changed to AKP-20 (manufactured by Sumitomo Chemical Co., Ltd., BET specific surface area: 4.3 m 2 / g), a disk-shaped phosphor plate having a plate thickness described in Table 1 was obtained in the same manner as in Test Example 1 except for the above.

[0099] (Test Example 4)

[0100] The alumina powder was changed to AA-03 (manufactured by Sumitomo Chemical Co., Ltd., BET specific surface area: 5.2 m 2 / g), a disk-shaped phosphor plate having a plate thickness described in Table 1 was obtained in the same manner as in Test Example 1 except for the above.

[0101] (Test Example 5)

[0102] The alumina powder was changed to AKP-53 (manufactured by Sumitomo Chemical Co., Ltd., BET specific surface area: 11.7 m 2 / g), a disk-shaped phosphor plate having a plate thickness described in Table 1 was obtained in the same manner as in Test Example 1 except for the above.

[0103] [Absorption rate]

[0104] The absorbance at 455 nm and 700 nm of the phosphor plate obtained in each test example was measured using a quantum efficiency measurement device (QE-2100HMB manufactured by Otsuka Electronics Co., Ltd.) having a system for evaluating reflected fluorescence and transmitted fluorescence independently. The absorbance at 455 nm was defined as A. 455 (%), the absorbance at 700 nm is set as A 700 (%), when the thickness of the phosphor plate is T (mm), calculate (A 700 / A 455 The results are shown in Table 1.

[0105] Based on Table 1 (A 700 / A 455 ) / T, Test Examples 1 to 4 are referred to as Examples 1 to 4, and Test Example 5 is referred to as Comparative Example 1.

[0106] [Table 1]

[0107]

[0108] The obtained phosphor plates were evaluated based on the following evaluation items.

[0109] [Crystal structure analysis]

[0110] The phosphor plates of Examples 1 to 4 were crushed in a mortar to prepare powdered samples, and the diffraction patterns of the obtained samples were measured using an X-ray diffractometer (product name: Ultima IV, manufactured by Rigaku Corporation), and the results confirmed the presence of a crystalline phase in the alumina sintered body. It was found that the crystalline phase contained α-alumina and Ca-α-sialon phosphor as the main phase, and γ-alumina was slightly mixed.

[0111] [Evaluation of optical properties]

[0112] The fluorescence intensity of the phosphor plates obtained in the respective Examples and Comparative Examples was measured by the following procedure.

[0113] The optical characteristics of the phosphor plate were measured using a chip-on-board (COB) type LED package 130 . Figure 3 It is a schematic diagram of a device (LED package 130 ) for measuring the emission spectrum of the phosphor plate 100 .

[0114] First, the phosphor plate 100 of each example and comparative example and the aluminum substrate (substrate 30) having the recessed portion 70 formed therein were prepared. The diameter of the bottom surface of the recessed portion 70 was set to The diameter of the opening of the recess 70 is 13.5 mm. It is 16mm.

[0115] Next, a blue LED (light emitting element 20 ) is mounted inside the recess 70 of the substrate 30 as a blue light source.

[0116] Then, a circular phosphor plate 100 is placed on the upper part of the blue LED so as to block the opening of the concave portion 70 of the substrate 30, and a Figure 3 The device shown (a chip-on-board (COB) type LED package 130).

[0117] Using the total luminous flux measurement system (HalfMoon / An integrating sphere system (manufactured by Otsuka Electronics Co., Ltd.) was used to measure the emission spectrum of the surface of the phosphor plate 100 when the blue LED of the manufactured LED package 130 was turned on.

[0118] In the obtained emission spectrum, the maximum fluorescence intensity (W / nm) of orange light (Orange) with a wavelength of 585nm to 605nm was determined. Table 1 shows the relative values ​​(%) of other examples and comparative examples with respect to the maximum fluorescence intensity when Example 1 was normalized as 100%.

[0119] The phosphor plates of Examples 1 to 4 showed superior fluorescence intensity compared to Comparative Example 1.

[0120] This application claims the priority based on Japanese patent application No. 2019-120861 filed on June 28, 2019, and all the disclosed contents are incorporated into this specification.

[0121] Explanation of symbols

[0122] 10 Phosphor Plate

[0123] 20 Light-emitting element

[0124] 30 substrate

[0125] 40 Solder

[0126] 50 electrodes

[0127] 60 Bonding wire

[0128] 70 recess

[0129] 100 Phosphor Plate

[0130] 100 Lighting Device

[0131] 120 Lighting Device

[0132] 130 LED Package

Claims

1. A phosphor plate comprising a plate-shaped composite body including a base material and a phosphor dispersed in the base material, The base material is composed of a sintered body of aluminum oxide. The content of the phosphor in the entire composite is 5 Vol% to 60 Vol%, The phosphor comprises an α-sialon phosphor, The total content of the α-sialon phosphor and the aluminum oxide is 95 to 100 Vol% in the entire composite. When the absorption spectrum of light with a wavelength of 300 nm to 700 nm is measured for this phosphor plate, the absorbance at 455 nm is defined as A. 455 (%), the absorbance at 700 nm is set as A 700 (%), when the thickness of the phosphor plate is T (mm), (A 700 / A 455 ) / T satisfies 0.01~1.

00.

2. The phosphor plate according to claim 1, wherein: The thermal conductivity of the phosphor plate is 10 W / m·K to 40 W / m·K.

3. The phosphor plate according to claim 1 or 2, which is used as a wavelength converter that converts irradiated blue light into orange light to emit light.

4. A light emitting device comprising: A Group III nitride semiconductor light emitting device, and The phosphor plate according to claim 1 or 2 is provided on one surface of the Group III nitride semiconductor light-emitting device.

Citation Information

Patent Citations

  • Semiconductor light-emitting device

    JP2012009470A

  • toner

    JP2019120861A

  • Semiconductor light-emitting devices

    CN102299237A

  • Method for producing wavelength converting member, and wavelength converting member

    CN109837085A